MENDALAMI KONSEP NUSYUZ DAN SYIQAQ DALAM PERSPEKTIF HUKUM ISLAM: SEBAB, DAMPAK, DAN SOLUSI - Masri, Masri (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
Nusyuz and syiqaq are two essential concepts in Islamic law related to the dynamics of marital conflict. This article aims to delve into the meanings, causes, impacts, and solutions surrounding these two issues. From an Islamic perspective, nusyuz refers to the disobedience of either party, whether the wife or husband, in fulfilling their marital obligations, while syiqaq refers to disputes that can lead to the breakdown of the household. Using a descriptive-analytical approach, this article examines relevant verses of the Qur'an, hadiths, and scholarly opinions on nusyuz and syiqaq. It is hoped that this article will contribute to understanding and promoting preventive and solution-oriented efforts to maintain harmony within marriage.